Antimicrobial surfaces for use on inhabited space craft: A review. (August 2020) - Paton, Susan; Moore, Ginny; Campagnolo, Lucie; Pottage, Thomas
Abstract: Biodegradation of materials on crewed spacecraft can cause disruption, loss of function and lost crew time. Cleaning of surfaces is only partially effective due in accessibility and resource concerns. Commonly affected surfaces are hand-touch sites, waste disposal systems and liquid-handling systems, including condensing heat exchangers. The use of materials on and within such affected systems that reduce the attachment of and degradation by microbes, is an innovative solution to this problem. This review aims to examine both terrestrial and space-based experiments that have aimed to reduce microbial growth which are applicable to the unique conditions of crewed spacecraft. Traditional antimicrobial surfaces such as copper and silver, as well as nanoparticles, long-chain organic molecules and surface topographical features, as well as novel "smart" technologies are discussed. Future missions to cis-lunar and Martian destinations will depend on materials that retain their function and reliability for their success; thus, the use of antimicrobial and antifouling materials is a pivotal one.